![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
先化简,再求值:1-[(x)-1/1-x]2除以x2-x+1/x2-2x+1,其中x2-x+5=0
展开全部
解:
原式=1-[(x)-1/(1-x)]²÷[(x²-x+1)/(x²-2x+1)]
=1-[x(1-x)/(1-x)-1/(1-x)]²÷[(x²-x+1)/(x-1)²]
=1-[(x-x²-1)/(1-x)]²返汪凯×[(x-1)²/(x²-x+1)]
=1-[(x²-x+1)/(x-1)]²×[(x-1)²/(x²-x+1)]
=1-[(x²-x+1)²/(x-1)²]×[(x-1)²/(x²-x+1)]
=1-(x²-x+1)
=-(x²-x)
∵ x²-x+5=0
∴陵野 x²-x=-5
原漏唤式=-(-5)
=5
原式=1-[(x)-1/(1-x)]²÷[(x²-x+1)/(x²-2x+1)]
=1-[x(1-x)/(1-x)-1/(1-x)]²÷[(x²-x+1)/(x-1)²]
=1-[(x-x²-1)/(1-x)]²返汪凯×[(x-1)²/(x²-x+1)]
=1-[(x²-x+1)/(x-1)]²×[(x-1)²/(x²-x+1)]
=1-[(x²-x+1)²/(x-1)²]×[(x-1)²/(x²-x+1)]
=1-(x²-x+1)
=-(x²-x)
∵ x²-x+5=0
∴陵野 x²-x=-5
原漏唤式=-(-5)
=5
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询